Compositions for medicinal Chemistry of fullerenes - Sheka, E.F. (Хімія, фізика та технологія поверхні, 2010)
The paper presents a quantum-chemical approach to two aspects of fullerene nanomedicine related to the oxidative and antioxidant actions of fullerene. The first topic is concerned in regards photodynamic therapeutic effect of fullerene solutions. A new mechanism of the effect is proposed. The second aspect is exemplified by the consideration of two fullerene-silica complexes, namely, fullerosil and fullerosilica gel.